AKSESIBILITAS JURU BAHASA ISYARAT (JBI) DALAM PRAKTIK IJAB QOBUL BAGI PENYANDANG DISABILITAS RUNGU PERSPEKTIF HUKUM ISLAM - Ahmad Nur Fadloli; Idarotul Nginayah (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2023)
Ijab qobul is one of the pillars of marriage. The pronunciation must be done in one assembly, either directly or with a separation that does not cause the contract to be broken. The pronunciation of the ijab must use pronunciations that indicate the meaning of marriage and must be understood by the groom before expressing his consent to marriage. Judging from Islamic law, the translation of the pronunciation of the consent as previously explained is permissible and the marriage contract remains valid. Even if the translation is considered a